Edukasi preventif dan promotif dalam upaya pencegahan stunting di Desa Tuncung Kecamatan Maiwa Kabupaten Enrekang - Syamson, Meriem Meisyaroh; Zainab, Zainab; Hasanuddin, Indirwan; Sulaeman, Sulaeman; Purnama AL, Jumiarsih; Murtini, Murtini; Faridah, Faridah; Suparta, Suparta (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Stunting is a public health problem that is still a serious challenge in Indonesia. Stunting occurs due to chronic malnutrition which causes children to have a lower height compared to children of the same age. The prevalence of stunting in Indonesia is still quite high, although efforts to reduce it have been carried out nationally. This condition not only has an impact on children's physical condition, but also affects their cognitive development, immunity, and productivity in the future. Purpose: To provide education with a preventive approach and a promotive approach to the community in an effort to prevent stunting incidents in a sustainable manner. Method: The target of this activity is all residents of Tuncung Village, especially housewives and those with babies and children. On Wednesday, January 8, 2025, at the Tuncung Village Hall, Maiwa District, Enrekang Regency. Counseling by providing information directly by health workers or facilitators to the community in the form of lectures to provide basic knowledge about stunting, such as causes, impacts, and how to prevent it Results: The participants gave a positive response by attending and following each activity session, were able to provide simulation actions according to the instructions after gaining knowledge from the presentation of the material provided by the resource person, understood efforts to prevent stunting with awareness as preventive measures such as fulfilling balanced nutrition, good parenting patterns, and environmental cleanliness, understood promotive efforts in reducing the incidence of stunting by changing positive behavior, namely playing an active role in monitoring the growth and development of children through routine visits to health facilities. Conclusion: Education and preventive approaches provide increased knowledge in identifying and reducing the risk of stunting early on. Meanwhile, promotive education increases public awareness of the importance of a healthy lifestyle, exclusive breastfeeding and good parenting in supporting child growth and development in an effort to prevent stunting. Preventive and promotive education will reduce stunting incidents sustainably. Suggestion: Introduce the concept of